The distribution of household debt in the United States, 1950-2022 - Alina K. Bartscher; Moritz Kuhn; Moritz Schularick; Ulrike I. Steins (Review of Economic Dynamics, 2025)
Using new household-level data, we study the secular increase in U.S. household debt and its distribution since 1950. Most of the debt were mortgages, which initially grew because more households borrowed. Yet after 1980, debt mostly grew because households borrowed more. We uncover home equity extraction, concentrated in the white middle class, as the largest cause, strongly affecting intergenerational inequality and life-cycle debt profiles. Remarkably, the additional debt did not lower households' net worth because of rising house prices. We conclude that asset-price-based borrowing became an integral part of households' consumption-saving decisions, yet at the cost of higher financial fragility.
Keywords: G51; E21; E44; D14; D31; 330; Household debt; Home equity extraction; Inequality; Household portfolios